Accuracy of Clinical Coding in Cesarean Section Cases Using ICD-10 and ICD-9-CM - Gama Bagus Kuntoadi; Indah Kristina; Hudiyati Agustini; Rumondang Christin (Journal Medical Informatics Technology, 2026)
Accurate clinical coding in cesarean section cases is essential for morbidity reporting, clinical data quality, and the validity of INA-CBG reimbursement claims under the national health insurance system. Obstetric cases are inherently complex, involving multiple diagnosis and procedure codes that must conform to ICD-10 and ICD-9-CM standards. Objective: This study aimed to analyze the accuracy of ICD-10 diagnosis coding and ICD-9-CM procedure coding across multiple obstetric coding components in cesarean section cases at a hospital in Jakarta, Indonesia. A descriptive quantitative study with a retrospective design was conducted on 95 medical records of obstetric and gynecological patients who underwent cesarean section in 2025, selected through total sampling. Coding accuracy was determined by comparing hospital-assigned codes against standard codes re-verified by researchers based on WHO ICD-10 Volume 2 and ICD-9-CM guidelines. Data were analyzed using frequency, percentage, mean, median, and standard deviation, following a Shapiro-Wilk normality test. The overall accuracy rate for ICD-10 diagnosis codes was 83.9% (266/317 codes) and for ICD-9-CM procedure codes was 91.5% (86/94 codes). Accuracy varied substantially across coding components: secondary diagnosis codes for cesarean delivery and delivery outcome codes each reached 90.5%, while codes for concomitant diagnoses reached only 34.7%. For procedures, cesarean section codes (74.x) achieved 85.3% accuracy, whereas non-cesarean section procedure codes showed accuracy of only 5.3%, predominantly due to undercoding of additional operative procedures documented in surgical reports. Coding accuracy for obstetric cesarean section cases was generally good to very good in aggregate; however, substantial gaps remain in the coding of concomitant diagnoses and additional procedures. This study contributes a component-level evaluation across diagnosis, delivery outcome, and procedure coding, offering a more granular assessment of coding accuracy than prior single-metric studies.